2022
DOI: 10.3389/fdgth.2022.1027864
|View full text |Cite
|
Sign up to set email alerts
|

E-mental health implementation in inpatient care: Exploring its potential and future challenges

Abstract: BackgroundThere is a great evidence base today for the effectiveness of e-mental health, or the use of technology in mental healthcare. However, large-scale implementation in mental healthcare organisations is lacking, especially in inpatient specialized mental healthcare settings.AimThe current study aimed to gain insights into the factors that promote or hinder the implementation of e-mental health applications on organisational, professional and patient levels in Belgium.MethodsFour Belgian psychiatric hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Two recent international implementation studies in Belgium [ 16 ] and Canada [ 17 ] emphasized hindering factors regarding the implementation process of internet-based applications in inpatient mental healthcare settings. Professionals mentioned high patient turnover in the acute inpatient setting [ 16 ], lack of time and a high workload for professionals, technical difficulties and insufficient structural facilities for the use of e-mental health as barriers [ 17 ]. Insufficient staff qualification, lack of training and supervision, and other organizational and administrative factors may also hinder the clinical implementation of internet-based applications [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent international implementation studies in Belgium [ 16 ] and Canada [ 17 ] emphasized hindering factors regarding the implementation process of internet-based applications in inpatient mental healthcare settings. Professionals mentioned high patient turnover in the acute inpatient setting [ 16 ], lack of time and a high workload for professionals, technical difficulties and insufficient structural facilities for the use of e-mental health as barriers [ 17 ]. Insufficient staff qualification, lack of training and supervision, and other organizational and administrative factors may also hinder the clinical implementation of internet-based applications [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Becker and colleagues [ 29 ] showed that the number of diagnoses and symptom severity were associated with active or inactive participation in an online intervention during and after inpatient and day-clinic psychotherapeutic treatment. A lack of motivation due to symptom severity was also a reason for patients to decline participation in an inpatient study on e–mental health implementation by Van Assche et al [ 30 ]. According to Wentzel and colleagues [ 31 ], crisis risk and psychosocial problems are important factors to consider for a fit for blended treatment.…”
Section: Introductionmentioning
confidence: 99%